Relationships Between Gender and Alberta Achievement Test Scores During a Four-Year Period - Pope, Gregory A.; Wentzel, Carolyn; Braden, Brigitta; Anderson, Jordan (Alberta Journal of Educational Research, 2006)
The purpose of this study was to investigate statistical relationships between gender and Alberta Achievement Testing Program scores. Achievement test scores from grades 3, 6, and 9 in all subject areas were investigated during a four-year period. Results showed statistically significant positive correlations between gender and scores in most subject areas. Girls tended to outperform boys in language-based tests (i.e., writing and reading assignments), whereas boys tended to score higher than girls in mathematics and science. Correlation effect sizes were in the small range for the machine-scored components and near the medium size range for the constructed-response components. In general, the results show that small relationships exist between gender and achievement test scores in Alberta.